Proyeksi Potensi Fiskal DKI Jakarta 2018-2022 - Yurianto Yurianto (Universitas Muhammadiyah Prof. DR HAMKA., 2018)
The purpose of this study was to determine the fiscal potency of DKI Jakarta on 2018-2022 which cover Total Owned Resource Revenue, Fiscal Capacity, Total Revenue, Fiscal Gap, Economic Growth, Total Expenditure and Total Gross Domestic Regional Product of DKI Jakarta. This study use quantitative approach to obtain optimal results. This approach use simultaneously equation model. Simultaneously equation model are divided into five block consisting of thirty-three equation, which nineteen of them are structural equation and fourteen of them are identity equation. The results of this study showed quite promising number on economic growth of Jakarta in 2018-2022. However inflation also shows increasing number. Therefore this study recommended, for eco-nomic growth continous to grow on quality then inflation control should continue to be done with various policies especially distribution policies.